Liquidity regulations, bank lending and fire-sale risk - Roberts, Daniel T.; Sarkar, Asani; Shachar, Or (Journal of Banking & Finance, 2023)
We examine whether U.S. banks subject to the Liquidity Coverage Ratio (LCR) reduce lending (an unintended consequence) and/or become more resilient to liquidity shocks, as intended by regulators. We find that LCR banks tighten lending standards, and reduce liquidity creation that occurs mainly through lower lending relative to non-LCR banks. However, covered banks also contribute less to fire-sale externalities relative to exempt banks. For LCR banks, we estimate that the total after-tax benefits of reduced fire-sale risk (net of the costs associated with foregone lending) exceed $50 billion from 2013Q2 to 2017, mostly accruing to the largest LCR banks. Non-LCR regulations enacted during our sample period cannot fully account for these findings. For the banking sector as a whole, lending migrates to smaller, non-LCR banks so that lending shares increase but fire-sale risk does not decrease. Our results highlight the trade-off between liquidity creation and resiliency arising from liquidity regulations that underlie the debate on whether the LCR should be extended following the banking crisis of March 2023.